Discourse Context in the Novel Heartbreak Motel by Ika Natassa Published 2022 - Nurhayati, Dwi Astuti Wahyu; Situmorang, Mulkan Andika; Ramadhani, Mastari; Gusar, Martua Reynhat Sitanggang; Nasution, Izmawal Pebriani (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Motel. This study uses a qualitative approach and content analysis method. The data source in this study is the novel Heartbreak Motel by Ika Natassa. The data in this study are in the form of quotations containing discourse contexts including the context of the background (setting and scene), the context of participants (participants), the context of results (ends), the context of the mandate (act), the context of the method (key), the context of means (instruments), the context of norms (norms), and the context of types (genres) in the novel Heartbreak Motel by Ika Natassa. Data collection was obtained by reading, finding/marking, copying and grouping words included in the discourse context. The results of this study found 34 scenes containing eight elements of discourse context, namely the context of the background (setting and scene) as many as 41 data consisting of 17 time setting data and 24 place setting data, the context of participants (participants) as many as 22 participants, the context of results (ends) as many as 29 data, the context of the mandate (act) as many as 15 data, the context of the method (key) as many as 28 data, the context of the means (instrument) in the discourse is carried out verbally or directly as many as 28 data and using telephone media as many as 6 data, the context of norms (norms) in the discourse is carried out in two directions and three directions, and the context of the type (genre) in the discourse is included in fictional prose.